PERBANDINGAN EFEKTIVITAS DIAGRAM KONTROL DECISION ON BELIEF DAN DIAGRAM KONTROL P PADA PENGENDALIAN KUALITAS PRODUK BATA RINGAN DI PT. BUMI SARANA BETON - Asmi, Nia Nurul; Sudarmin, Sudarmin; Rais, Zulkifli (Program Studi Statistika Fakultas MIPA UNM, 2024)
Statistical quality control is a useful effort to monitor, control, analyze, manage, and improve products and processes using statistical methods. One of the tools used in statistical quality control is a control chart, which is a graph to show whether the performance of a process can maintain an acceptable level of quality with the aim of monitoring process shifts. P control charts and DOB control charts are diagrams used for attribute data. The DOB control chart is a new method with a Bayesian approach. Therefore, a comparison of the two control charts was carried out to determine which one had a better level of effectiveness in controlling the quality of light brick production at PT. Bumi Sarana Beton. The data used in this research is daily data on the production of light brick defects during May 2023. The results obtained are the production of light bricks at PT. Bumi Sarana Beton has not been statistically controlled using p control chart because there are four points out of control. Meanwhile, by using the DOB control chart, light brick production at PT. Bumi Sarana Beton has been statistically controlled because it did not occur out of control. Hence, the p control chart it can be said to have better effectiveness because it can detect more sensitively at 13.34% of points out of control compared to the DOB control chart on quality control of light brick products at PT. Bumi Sarana Beton